2021
DOI: 10.3390/s21041467
|View full text |Cite
|
Sign up to set email alerts
|

Integration of Blockchain, IoT and Machine Learning for Multistage Quality Control and Enhancing Security in Smart Manufacturing

Abstract: Smart manufacturing systems are growing based on the various requests for predicting the reliability and quality of equipment. Many machine learning techniques are being examined to that end. Another issue which considers an important part of industry is data security and management. To overcome the problems mentioned above, we applied the integrated methods of blockchain and machine learning to secure system transactions and handle a dataset to overcome the fake dataset. To manage and analyze the collected da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
61
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 104 publications
(61 citation statements)
references
References 67 publications
(43 reference statements)
0
61
0
Order By: Relevance
“…There has been a recent study to evaluate multi-level quality control based on various machine learning and blockchain-based solutions [30]. The authors found that XGBoost performs well by comparing the accuracy, precision, and recall of XGBoost and KNN algorithms.…”
Section: Machine Learningmentioning
confidence: 99%
“…There has been a recent study to evaluate multi-level quality control based on various machine learning and blockchain-based solutions [30]. The authors found that XGBoost performs well by comparing the accuracy, precision, and recall of XGBoost and KNN algorithms.…”
Section: Machine Learningmentioning
confidence: 99%
“…This section presents a detailed explanation of the existing studies in smart home security based on IoT [25][26][27][28][29][30][31], blockchain, and machine learning [10,[32][33][34][35][36][37][38][39][40]. Due to the flexibility of the blockchain framework, a smart home ecosystem can shape easily.…”
Section: Related Workmentioning
confidence: 99%
“…However, security is the biggest issue in application partitioning when it runs on different computing nodes and shares data between connected computing nodes for execution [4]. Many security schemes have been suggested in MECCA to support application data in the network [5]. For instance, RSA, CBC, SHA-256, and MD5 are based on both symmetric and asymmetric schemes.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, RSA, CBC, SHA-256, and MD5 are based on both symmetric and asymmetric schemes. Many studies [5][6][7][8][9][10] have adopted these methods in MECCA for the application-partitioning problem in a distributed network. The primary goal of this study was to undertake encryption and decryption on the local machine to ensure the security of data before offloading to the edge-cloud network.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation